Job satisfaction among the bankers: an investigation on Maybank Islamic in Pahang / Nur Aini Najma Rashidi - Rashidi, Nur Aini Najma (Faculty of Business Management, University Teknologi MARA, 2018)
Banking industry is one of the major industries for country's economic development. The purpose of this research paper is to examine the factors that influencing job satisfaction among the bankers where it expected to lead toward better quality work performance and higher commitment from workers. This study was conducted to investigate the most significant relationship between the factors that lead to job satisfaction among the bankers in Maybank Islamic Berhad. This study has focused on individual who are worked at Maybank Islamic which is focus to four branches at Triang, Temerloh, Mentakab and Jengka in Pahang. A structured questionnaire survey was collected by using convenience sampling technique. The researcher has been distributed about 100 of questionnaires to the employees of Maybank Islamic Berhad within the period of one month. The research method that had been used in this study is frequencies analysis. descriptive analysis, correlation analysis, regression analysis and reliability analysis that which has been analysed by using a statistical package for social science (SPSS) 22. The researcher have also conducted pilot test for preliminary test on these factors. The factor consists of five main items which are remuneration, organisation behaviour, working environment, recognition and job security. The results obtained from analysis of data revealed that organisation behaviour, working environment and job security have more influenced than the factors of remuneration and recognition in determining job satisfaction of Maybank Islamic bankers. There are some suggestions for further research and improvement for getting better result.